Village Financial Information System in Salibabu Island: The Phenomenon of Structural Success - Ignatius Novianto Hariwibowo; Christophorus Heni Kurniawan (Universitas Pendidikan Indonesia, 2024)
The purpose of this study is to describe the adoption process of the Village Financial System (Siskeudes) on Salibabu Island, Talaud Island. Interviews with ten village heads were used to obtain the research data. The interview results were processed using a topic analysis approach based on Social Network Analysis. The results of this study show that the ease of obtaining the benefits of Siskeudes is the dominant factor in the success of Siskeudes adoption. This research shows that convenience is a factor shaped through structures manifesting in intensive training support and tools. Internal government structure support is essential because of the response to the benefits of technology adopted by central and local governments. For accounting science, the results of this study show that digitalization can support the realization of village financial management accountability. The adaptability of digital change in the village government is formed from a strong government structure. Village digital change can be achieved by strengthening the government structure by making the sub-district government an internal change agent, which is realized through intense mentoring. The goal is to internalize the benefits so that they become part of the village administrative structure. This study used topic analysis that had not been done by previous research in phenomenology research.